Evaluation of Feulgen Reaction for Quantitative DNA Analysis in Oral Leukoplakia: Insights into Malignant Transformation Risk - Amit Kumar Srivastava; Ruchi Jain; Aishwarya Srivastava; Swati Shrivastava (Journal of Pharmacy and Bioallied Sciences)
Background: Oral leukoplakia is a potentially malignant disorder with a significant risk of transformation into oral squamous cell carcinoma. The Feulgen reaction, a DNA-specific staining technique, has been widely used for the quantitative analysis of DNA content in various tissues. Materials and Methods: A total of 50 patients diagnosed with oral leukoplakia were selected for the study. Biopsy samples were obtained from the lesions, and the Feulgen reaction was performed to stain the DNA. Quantitative DNA analysis was conducted using image cytometry, measuring the integrated optical density (IOD) of Feulgen-stained nuclei. The samples were categorized based on their DNA content into diploid, aneuploid, and tetraploid groups. Statistical analysis was performed to assess the correlation between DNA content and the histopathological grading of the lesions. Results: Out of the 50 samples, 30% (n = 15) exhibited diploid DNA content, 50% (n = 25) were aneuploid, and 20% (n = 10) were tetraploid. A significant correlation was found between aneuploid DNA content and higher grades of dysplasia (P < 0.05). The mean IOD values for diploid, aneuploid, and tetraploid samples were 1.2, 2.8, and 3.5, respectively. Patients with aneuploid DNA content demonstrated a higher risk of malignant transformation compared to those with diploid DNA content. Conclusion: The Feulgen reaction, combined with quantitative DNA analysis, is a valuable tool in assessing the malignant transformation risk in oral leukoplakia. The presence of aneuploidy in these lesions is significantly associated with higher dysplastic changes and an increased risk of progression to oral cancer. Further studies with larger sample sizes are recommended to validate these findings and to establish the Feulgen reaction as a standard predictive marker in clinical practice.